The Contribution of Pangestu Semarang Branch 3 in Strengthening of Character Education (PPK) Based on the Teachings of Sang Guru Sejati - Sri Sulistyaningsih; Tri Joko Raharjo; Agus Hermanto; Titi Prihatin (Universitas Negeri Semarang, 2021)
This study aims to find out how the implementation of community-based PPK in a qualitative research, with the research subject being a non-formal education center, namely Pangestu Psychological Organization Semarang Branch 3, which has consistently carried out education of noble character and character building. Collecting data using observation, interviews and documentation methods. The data that has been collected was analyzed using descriptive analysis. The teachings of Sang Guru Sejati, namely Hasta Sila (The Eight Kinds of Main Characters), Paliwara (The Five Prohibitions of God) and Jalan Rahayu (The Five Fold Safe Paths), as well as an understanding of the Pangestu Dasa Sila Guidelines as an attitude of inner and outer life and an understanding of Candra Jiwa Indonesia (CJI) which describes structure of the human soul. This structure of the human soul is part of the Teachings of Sang Suksma Sejati / Sang Guru Sejati which is multicultural, scientific and universal. The main Teachings of Sang Suksma Sejati / Sang Guru Sejati, which function as strengthening of character education, are given by using the Olah Rasa method at the Pangestu Psychological Organization Semarang Branch 3. The results of this study can be applied massively and become a reference in further research on Strengthening of Character Education based on the Teachings of Sang Suksma Sejati / Sang Guru Sejati (The True Teacher).